Metal-loaded three-dimensional copper-based catalyst as well as preparation method and application thereof

By forming Cu(OH)2 nanowires and cuprous oxide on the copper foam, and reacting with metal ions, a metal-loaded three-dimensional copper-based catalyst is prepared, which solves the problem of preparing multi-metal element-Cu(OH)2 in the existing technology. The problems of inconvenient operation and high energy consumption when composite materials are used to achieve efficient electrocatalytic performance.

CN119352092AActive Publication Date: 2025-01-24XIAN UNIV OF TECH

Patent Information

Application Number
CN202411787862.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-01-24
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

In the prior art, when preparing polymetallic element-Cu(OH)2 composite materials, electrochemical deposition method and high temperature sintering method have problems such as inconvenient operation, high energy consumption and low catalytic performance.

Method used

Use foam copper as the base, soak in a mixed solution containing ammonium sulfate and sodium hydroxide, and control the dry conditions, obtain CU (OH) 2 nano wines and copper oxide, and then react with metal ions to prepare metal loads Three -dimensional copper catalyst.

Benefits of technology

The composite of multi-metal elements and Cu(OH)2 is realized under normal temperature and pressure, overcoming the shortcomings of the existing technology. The obtained catalyst has efficient mass transfer and charge transfer performance, and significantly improves the application efficiency of electrocatalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119352092A_ABST
    Figure CN119352092A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electro-catalysis electrode materials, in particular to a metal-loaded three-dimensional copper-based catalyst and a preparation method and application thereof. The preparation method comprises the following steps: by taking foamy copper as a substrate, firstly soaking the foamy copper in a mixed solution containing ammonium persulfate and sodium hydroxide, then taking out the foamy copper and controlling drying conditions, while obtaining Cu (OH) 2 nanowires on the foamy copper, realizing dehydration reduction of part of Cu (OH) 2 to obtain cuprous oxide active sites with reducibility; cuprous oxide reacts with metal ions, and the metal-loaded three-dimensional copper-based catalyst is obtained. According to the invention, the compounding of multiple metal elements and Cu (OH) 2 is realized at normal temperature and normal pressure, the technical defects of an electrochemical deposition method and a high-temperature sintering method in the prior art are overcome, and the obtained metal-loaded three-dimensional copper-based catalyst has the characteristics of no aggregation of metal particles, high-efficiency mass transfer and load transfer, and good application prospect. The application efficiency of electro-catalysis of the metal-loaded three-dimensional copper-based catalyst can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrocatalytic electrode materials, and in particular to a metal-supported three-dimensional copper-based catalyst and a preparation method and application thereof. Background Art

[0002] Ammonia plays an important role in various fields and is considered to be a transportable carbon-free energy carrier. The main industrial method for producing NH3 in the world today is still the Haber-Bosch process. However, this process requires reactions under high pressure of 20MPa~30MPa and high temperature of 300℃~500℃, which will lead to a large amount of energy consumption and greenhouse gas emissions. Electrocatalytic reduction of nitrates to produce ammonia is a green and environmentally friendly technology. Its mechanism is to convert nitrates, which pose a serious threat to human health and ecosystems, into ammonia with high economic value by applying current at the cathode, showing the application prospect of "killing two birds with one stone". In this process, the choice of electrode materials is crucial, which directly affects the efficiency and selectivity of electrocatalytic reduction.

[0003] Copper-based materials have become a hot topic of research due to their inherent advantages of nitrate reduction electrocatalysis, such as good conductivity and weak hydrogen evolution ability. Shen et al. demonstrated that micron-sized Cu2O / Cu dendrites can be generated on a copper foam mesh in a copper sulfate and sulfuric acid solution by electrochemical deposition, thereby increasing the nitrate reduction rate from 84% to 98.9%. The specific disclosure is in “ZR Shen, JB Yan, M Wang, LD Xing, et al., Cu / Cu +Synergetic Effect in Cu2O / Cu / CF Electrocatalysts for Efficient Nitrate Reduction to Ammonia, ACSSustainable Chem. Eng, 202311(25)9433-9441”; Xu et al. demonstrated that by adopting the impregnation-high temperature sintering method, copper-based oxide nanoarrays can be generated on the foam copper mesh, and by modifying the surface with conductive polymers, the performance of nitrate reduction to ammonia can be improved, which is specifically disclosed in “Y.Xu, Y.Wen, T.Ren, et al., Engineering the surface chemical microenvironment over CuO nanowire arrays by polyaniline modification for efficient ammonia electrosynthesis from nitrate, Applied Catalysis B: Environmental, 2023, 320, 121981”; In order to further optimize the nitrate adsorption and conversion of copper-based catalytic electrodes and improve the selectivity of synthetic ammonia, Au, Ru or Pd and Cu-based composite materials can be generated by electrodeposition or high-temperature ion replacement, which is specifically disclosed in “YK Zha, M Liu, JL Wang, et al., Electrochemical ammonia synthesis by reduction of nitrate on Au doped Cunanowires, RSC Adv., 2023, 13, 9839-9844”; “FY., Wu, ZY., Gupta, S. et al., Efficient conversion of low-concentration nitrate sources into ammonia on a Ru-dispersed Cunanowire electrocatalyst. Nat. Nanotechnol. 2022, 17, 759-767”; “W. Gao, J. Sun, G. Zhao, Pd Clusters Loaded with Multivalent Cu Foam for SuperiorElectrochemical Nitrate Reduction and Selective N≡N Bond Formation.Small,2024,20,2310597".

[0004] However, it can be seen from the above that the existing methods for preparing multi-metal element-Cu(OH)2 composite materials are mostly electrochemical deposition and high-temperature sintering. Among them, the electrochemical deposition method depends on the composition, pH value, temperature and current density of the electrolyte, so real-time regulation is required, which is inconvenient to operate; the high-temperature sintering method requires high temperature conditions, has high requirements on equipment, and requires inert gas assistance. In the process of large-scale industrial production, a large amount of energy consumption and CO2 emissions will be generated, which is not conducive to the optimization of the green energy system; in addition, the two also have a common defect, that is, the obtained metal particles are easy to aggregate, resulting in fewer active sites, thereby making the surface activity of the metal low, affecting the catalytic performance of the metal.

[0005] Based on the above reasons, it is of great significance to provide new methods to develop new multi-metal element-Cu(OH)2 composite materials. Summary of the invention

[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a metal-supported three-dimensional copper-based catalyst and a preparation method and application thereof. The present invention uses copper foam as a substrate, first immerses the copper foam in a mixed solution containing ammonium persulfate and sodium hydroxide, then takes it out and controls the drying conditions to obtain Cu(OH)2 nanowires on the copper foam while achieving dehydration reduction of a small portion of Cu(OH)2, and obtains reducing cuprous oxide, and then uses cuprous oxide to react with metal ions to obtain a metal-supported three-dimensional copper-based catalyst. The present invention realizes the composite of multiple metal elements and Cu(OH)2 at room temperature and pressure, overcomes the technical defects of the electrochemical deposition method and high-temperature sintering method in the prior art, and the metal nanoparticles of the metal-supported three-dimensional copper-based catalyst obtained by the method of the present invention do not aggregate, have the characteristics of efficient mass transfer and charge transfer, and can effectively improve the application efficiency of the electrocatalytic three-dimensional copper-based catalyst supported by the metal.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] The preparation method of a metal-supported three-dimensional copper-based catalyst comprises the following steps:

[0009] The foamed copper is immersed in a mixed solution containing ammonium persulfate and sodium hydroxide, then taken out and vacuum dried at 30°C to 90°C for 12h to 24h. Under this drying condition, Cu(OH)2 nanowires grow on the foamed copper, and a portion of the Cu(OH)2 undergoes dehydration and reduction to obtain Cu2O-Cu(OH)2 nanowires-foamed copper; if the vacuum drying temperature is lower than 30°C, the drying time is too long, affecting the production cycle; if the vacuum drying temperature is higher than 90°C, it will cause electrode ablation.

[0010] The Cu2O-Cu(OH)2 nanowire-foam copper is immersed in a metal solution and mixed, and the reducing Cu2O is used to undergo an oxidation-reduction reaction with the metal ions in the metal solution to reduce the metal ions to metals, thereby obtaining a metal-loaded three-dimensional copper-based catalyst. The entire preparation process of the present invention is carried out at room temperature and pressure, and the drying conditions are adjusted to obtain Cu2O, and then the Cu2O is used to reduce the metal ions to obtain a metal-loaded three-dimensional copper-based catalyst.

[0011] Preferably, the metal ions in the metal solution are selected from Pd 2+ 、Ru 3+ 、Au 3+ One or more of the .

[0012] Preferably, the molar concentration of metal ions in the metal solution is 2 mmol / L to 5 mmol / L. When the concentration is lower than 2 mmol / L, no metal particles are observed in the Cu(OH)2 nanowires; when the concentration is higher than 5 mmol / L, the structure of the Cu(OH)2 nanowires collapses and the catalytic performance decreases.

[0013] Preferably, the time for immersing the Cu2O-Cu(OH)2 nanowire-foam copper in the metal solution is 5 minutes to 30 minutes. The redox reaction between Cu2O and the metal ions in the metal solution is an instantaneous reaction, and the metal particle size and the catalytic electrode structure will change significantly with the change of immersion time, so the optimal redox reaction time is 5 minutes to 30 minutes.

[0014] Preferably, in the mixed solution, the concentration of sodium hydroxide is 0.8 mol / L to 1.5 mol / L, and the concentration of ammonium persulfate is 0.03 mol / L to 0.07 mol / L.

[0015] Preferably, the solvents of the mixed solution and the metal solution are both ultrapure water, and the resistivity of the ultrapure water is 18.25 MΩ·cm, which is in compliance with the industry standard for electrochemical experiments.

[0016] Preferably, the time for immersing the copper foam in the mixed solution is 25 minutes to 35 minutes. If the immersion time is too short, the Cu(OH)2 nanowires cannot be formed, and if the immersion time is too long, the structure of the Cu(OH)2 nanowires collapses.

[0017] Preferably, the copper foam is pickled before use to remove impurities and oxides on the copper foam.

[0018] The present invention also protects the metal-loaded three-dimensional copper-based catalyst obtained by the above-mentioned preparation method. In the metal-loaded three-dimensional copper-based catalyst, Cu(OH)2 nanowires are distributed on the foam copper, and one or more metal nanoparticles of Au, Ru, and Pd are located on the surface of the Cu(OH)2 nanowires.

[0019] The present invention also protects the use of metal-supported three-dimensional copper-based catalysts in the preparation of electrode materials for electrocatalytic reduction of nitrates to ammonia.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The present invention uses a simple infiltration method to prepare a metal-loaded three-dimensional copper-based catalyst at room temperature and pressure. Specifically, the copper foam is used as a substrate, and the copper foam is first immersed in a mixed solution containing ammonium persulfate and sodium hydroxide, and then taken out and vacuum dried at 30°C to 90°C by controlling the drying conditions. While obtaining Cu(OH)2 nanowires on the copper foam, the local Cu(OH)2 is dehydrated and reduced, and a reducing cuprous oxide is formed. At this time, the Cu(OH)2 nanowires are in situ grown on the copper foam, and then the cuprous oxide is used to perform an oxidation-reduction reaction with the metal ions in the metal solution. The oxidation-reduction reaction equation is: Cu2O+M 2+ +H2O→2Cu 2+ +2OH - +M,3 / 2Cu2O+H + +M 3+ +1 / 2H2O→3Cu 2+ +2OH - +M, to obtain metal-supported three-dimensional copper-based catalysts.

[0022] Compared with the electrochemical deposition method and high-temperature sintering method in the prior art, the present invention provides a new preparation principle. Under this technical principle, the preparation of multi-metal element-Cu(OH)2 composite materials at room temperature and pressure is realized, overcoming the technical defects of the electrochemical deposition method and high-temperature sintering method; and the present invention provides universal and mild preparation conditions, which has the advantages of simple process, low cost, controllable operation, high yield, environmental friendliness and high repeatability, and is convenient for subsequent industrial application.

[0023] The present invention prepares a metal-loaded three-dimensional copper-based catalyst, wherein Cu(OH)2 nanowires are distributed on the foamed copper, and one or more metal nanoparticles of Au, Ru, and Pd are located on the surface of the Cu(OH)2 nanowires. Small localized Cu2O is generated during vacuum drying, and metal ions undergo oxidation-reduction reactions on the Cu2O to form metal nanoparticles with a size of 20nm to 100nm. Since the overall synthesis process is not subjected to high-temperature sintering, the metal nanoparticles riveted in the Cu2O existing area will not migrate or agglomerate; in addition, in the metal-loaded three-dimensional copper-based catalyst, 0-dimensional metal nanoparticles are used to activate the chemical adsorption active sites of the catalytic reactants, one-dimensional Cu(OH)2 nanowires are used to enhance the coordinated regulation process of protons and charges during the reaction, and three-dimensional foamed copper is used as a metal electrode to optimize the reaction physical space and charge conduction capacity. The prepared metal-loaded three-dimensional copper-based catalyst has the characteristics of efficient mass transfer and charge transfer performance, so that it has more excellent electrocatalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 For the macro picture, Figure 1 Figure (a) shows the Cu2O-Cu(OH)2 nanowire-foam copper of Example 1. Figure 1 Figure (b) shows the Ru-supported three-dimensional copper-based catalyst of Example 1. Figure 1 Figure (c) shows the Pd-supported three-dimensional copper-based catalyst of Example 2. Figure 1 Figure (d) shows the Au-supported three-dimensional copper-based catalyst of Example 3. Figure 1 Figure (e) is a macroscopic image of the Au / Ru supported three-dimensional copper-based catalyst of Example 4.

[0025] Figure 2 Figure (a) is a SEM image of the Ru-supported three-dimensional copper-based catalyst of Example 1. Figure 2 Figure (b) is a particle size distribution diagram of Ru nanoparticles in the Ru-supported three-dimensional copper-based catalyst of Example 1. Figure 2 Figure (c) is the EDX image of the Ru-supported three-dimensional copper-based catalyst of Example 1.

[0026] Figure 3 Figure (a) is a SEM image of the Pd-supported three-dimensional copper-based catalyst of Example 2. Figure 3 Figure (b) is a diagram showing the particle size distribution of Pd nanoparticles in the Pd-supported three-dimensional copper-based catalyst of Example 2. Figure 3 Figure (c) is the EDX image of the Pd-supported three-dimensional copper-based catalyst of Example 2.

[0027] Figure 4 Figure (a) is a SEM image of the Au-supported three-dimensional copper-based catalyst of Example 3. Figure 4Figure (b) is a particle size distribution diagram of Au nanoparticles in the Au-supported three-dimensional copper-based catalyst of Example 3. Figure 4 Figure (c) is the EDX image of the Au-supported three-dimensional copper-based catalyst of Example 3.

[0028] Figure 5 Figure (a) is a SEM image of the Au / Ru-supported three-dimensional copper-based catalyst of Example 4. Figure 5 Figure (b) is a particle size distribution diagram of Au and Ru nanoparticles in the Au / Ru-supported three-dimensional copper-based catalyst of Example 4. Figure 5 Figure (c) is the EDX image of the Au / Ru supported three-dimensional copper-based catalyst of Example 4.

[0029] Figure 6 Figure (a) is a graph showing the nitrate conversion rate of the Ru-supported three-dimensional copper-based catalyst of Example 1, the Pd-supported three-dimensional copper-based catalyst of Example 2, the Au-supported three-dimensional copper-based catalyst of Example 3, the Au / Ru-supported three-dimensional copper-based catalyst of Example 4, and the foamed copper. Figure 6 Figure (b) is a graph of the synthetic ammonia production of the Ru-loaded three-dimensional copper-based catalyst of Example 1, the Pd-loaded three-dimensional copper-based catalyst of Example 2, the Au-loaded three-dimensional copper-based catalyst of Example 3, the Au / Ru-loaded three-dimensional copper-based catalyst of Example 4, and copper foam.

[0030] Figure 7 Figure (a) is a SEM image of the Au-supported three-dimensional copper-based catalyst of Example 5. Figure 7 Figure (b) is a particle size distribution diagram of Au nanoparticles in the Au-supported three-dimensional copper-based catalyst of Example 5. Figure 7 Figure (c) is a graph showing the nitrate conversion rate of the Au-supported three-dimensional copper-based catalyst of Example 5. Figure 7 Figure (d) is a graph showing the synthetic ammonia yield of the Au-supported three-dimensional copper-based catalyst of Example 5.

[0031] Figure 8 Figure (a) is a SEM image of the Ru-supported three-dimensional copper-based catalyst of Comparative Example 1. Figure 8 Figure (b) shows the nitrate conversion rate of the Ru-supported three-dimensional copper-based catalyst.

[0032] Fig. 9 This is a macroscopic image of the Au-supported three-dimensional copper-based catalyst of Comparative Example 2. DETAILED DESCRIPTION

[0033] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.

[0034] Compared with the high-temperature sintering method of the prior art, the present invention realizes the preparation of Cu-based hydroxide nanowires loaded with multiple metals without the assistance of reducing agents and surfactants at room temperature and pressure, thereby realizing the application of metal-loaded three-dimensional copper-based catalysts as highly active electrocatalytic reduction nitrate electrodes. In addition, the experimental process does not involve high-temperature sintering exceeding 100°C, which reduces energy consumption, avoids the aggregation and growth of metal nanoparticles during high-temperature sintering, and avoids the coating of organic surfactants, significantly increases the adsorption active sites of reactants during the catalytic process, and effectively improves the ammonia production efficiency of metal-loaded three-dimensional copper-based catalysts.

[0035] Compared with the electrochemical deposition method in the prior art, the present invention avoids the use of a large amount of high-concentration (>10mmol / L) metal ion solution as the electrolyte, thereby effectively reducing the preparation cost of the metal-loaded three-dimensional copper-based catalyst. On the other hand, the size of the Cu2O micro-region is controlled by the redox reaction between the Cu2O micro-region and the metal ions, and compared with the formation of micron-sized dendrites by electrochemical deposition, the particle size is miniaturized.

[0036] The technical solution of the present invention is studied using embodiments and comparative examples below, and the specific research methods and results are as follows:

[0037] Example 1

[0038] The preparation method of a metal-supported three-dimensional copper-based catalyst comprises the following steps:

[0039] S1. After pickling 2cm×1cm copper foam in 3mol / L dilute sulfuric acid solution for 30min, rinse with ultrapure water, dry at 60℃ for 6h, and take out to obtain clean copper foam.

[0040] S2. Soak the clean copper foam in a mixed solution containing 0.05 mol / L ammonium persulfate and 1 mol / L sodium hydroxide for 30 min, the volume of the mixed solution is 8 mL, then take it out and vacuum dry it at 30°C for 20 h to obtain Cu2O-Cu(OH)2 nanowire-copper foam, recorded as Cu2O-Cu(OH)2NW-CuCF.

[0041] S3. Immerse the Cu2O-Cu(OH)2NW-CuCF in 5 mL of a 2 mmol / L metal solution containing RuCl2 as the solute. After shaking for 30 min, rinse with ultrapure water and vacuum dry at 40 °C for 36 h to obtain a Ru-loaded three-dimensional copper-based catalyst, which is designated as Ru-Cu(OH)2NW-CuCF.

[0042] Example 2

[0043] The preparation method of a metal-supported three-dimensional copper-based catalyst comprises the following steps:

[0044] S1. After pickling 2cm×1cm copper foam in 3mol / L dilute sulfuric acid solution for 30min, rinse with ultrapure water, dry at 60℃ for 6h, and take out to obtain clean copper foam.

[0045] S2. Soak the clean copper foam in a mixed solution containing 0.03 mol / L ammonium persulfate and 0.8 mol / L sodium hydroxide for 30 min, the volume of the mixed solution is 8 mL, then take it out and vacuum dry it at 45°C for 12 h to obtain Cu2O-Cu(OH)2 nanowire-copper foam, recorded as Cu2O-Cu(OH)2NW-CuCF.

[0046] S3. Immerse the Cu2O-Cu(OH)2NW-CuCF in 5 mL of a 2 mmol / L metal solution containing PdCl2 as the solute. After reacting on a shaking table for 30 min, rinse with ultrapure water and then vacuum dry at 40 °C for 36 h to obtain a Pd-loaded three-dimensional copper-based catalyst, recorded as Pd-Cu(OH)2NW-CuCF.

[0047] Example 3

[0048] The preparation method of a metal-supported three-dimensional copper-based catalyst comprises the following steps:

[0049] S1. After pickling 2cm×1cm copper foam in 3mol / L dilute sulfuric acid solution for 30min, rinse with ultrapure water, dry at 60℃ for 6h, and take out to obtain clean copper foam.

[0050] S2. Soak the clean copper foam in a mixed solution containing 0.04 mol / L ammonium persulfate and 0.9 mol / L sodium hydroxide for 30 min, the volume of the mixed solution is 8 mL, then take it out and vacuum dry it at 30°C for 24 h to obtain Cu2O-Cu(OH)2 nanowire-copper foam, recorded as Cu2O-Cu(OH)2NW-CuCF.

[0051] S3. Immerse the Cu2O-Cu(OH)2NW-CuCF in 5 mL of a 2 mmol / L metal solution containing HAuCl4 as the solute. After shaking for 30 min, rinse with ultrapure water and vacuum dry at 40 °C for 36 h to obtain an Au-loaded three-dimensional copper-based catalyst, recorded as Au-Cu(OH)2NW-CuCF.

[0052] Example 4

[0053] The preparation method of a metal-supported three-dimensional copper-based catalyst comprises the following steps:

[0054] S1. After pickling 2cm×1cm copper foam in 3mol / L dilute sulfuric acid solution for 30min, rinse with ultrapure water, dry at 60℃ for 6h, and take out to obtain clean copper foam.

[0055] S2. Soak the clean copper foam in a mixed solution containing 0.06 mol / L ammonium persulfate and 1.1 mol / L sodium hydroxide for 30 min, the volume of the mixed solution is 8 mL, then take it out and vacuum dry it at 35°C for 18 h to obtain Cu2O-Cu(OH)2 nanowire-copper foam, recorded as Cu2O-Cu(OH)2NW-CuCF.

[0056] S3. Immerse the Cu2O-Cu(OH)2NW-CuCF in 5 mL of a 2 mmol / L metal solution containing RuCl2 and HAuCl4 as solutes. After shaking for 30 min, rinse with ultrapure water and vacuum dry at 40 °C for 36 h to obtain a metal-loaded three-dimensional copper-based catalyst, recorded as Au / Ru-Cu(OH)2NW-CuCF.

[0057] Example 5

[0058] The preparation method of a metal-supported three-dimensional copper-based catalyst comprises the following steps:

[0059] S1. After pickling 2cm×1cm copper foam in 3mol / L dilute sulfuric acid solution for 30min, rinse with ultrapure water, dry at 60℃ for 6h, and take out to obtain clean copper foam.

[0060] S2. Soak the clean copper foam in a mixed solution containing 0.04 mol / L ammonium persulfate and 0.9 mol / L sodium hydroxide for 30 min, the volume of the mixed solution is 8 mL, then take it out and vacuum dry it at 90°C for 12 h to obtain Cu2O-Cu(OH)2 nanowire-copper foam, recorded as Cu2O-Cu(OH)2NW-CuCF.

[0061] S3. Soak the Cu2O-Cu(OH)2NW-CuCF in 5 mL of a 2 mmol / L metal solution containing HAuCl4 as the solute. After shaking for 30 min, rinse with ultrapure water and vacuum dry at 40 °C for 36 h to obtain an Au-loaded three-dimensional copper-based catalyst, recorded as Au-Cu(OH)2NW-CuCF-90.

[0062] Example 6

[0063] The preparation method of a metal-supported three-dimensional copper-based catalyst comprises the following steps:

[0064] S1. After pickling 2cm×1cm copper foam in 3mol / L dilute sulfuric acid solution for 30min, rinse with ultrapure water, dry at 60℃ for 6h, and take out to obtain clean copper foam.

[0065] S2. Soak the clean copper foam in a mixed solution containing 0.07 mol / L ammonium persulfate and 1.5 mol / L sodium hydroxide for 30 min, the volume of the mixed solution is 8 mL, then take it out and vacuum dry it at 60°C for 14 h to obtain Cu2O-Cu(OH)2 nanowire-copper foam, recorded as Cu2O-Cu(OH)2NW-CuCF.

[0066] S3. Immerse the Cu2O-Cu(OH)2NW-CuCF in 5 mL, 5 mmol / L metal solution containing PdCl2 and RuCl2 as solutes. After shaking for 5 min, rinse with ultrapure water and vacuum dry at 40 °C for 36 h to obtain a Pd / Ru-loaded three-dimensional copper-based catalyst.

[0067] Comparative Example 1

[0068] The preparation method of a metal-supported three-dimensional copper-based catalyst comprises the following steps:

[0069] S1. After pickling 2cm×1cm copper foam in 3mol / L dilute sulfuric acid solution for 30min, rinse with ultrapure water, dry at 60℃ for 6h, and take out to obtain clean copper foam.

[0070] S2. Soak the clean copper foam in a mixed solution containing 0.05 mol / L ammonium persulfate and 1 mol / L sodium hydroxide for 30 min, the volume of the mixed solution is 8 mL, then take it out and vacuum dry it at 25° C. for 36 h to obtain an intermediate.

[0071] S3. The intermediate was immersed in 5 mL of a 2 mmol / L metal solution containing RuCl2 as the solute. After shaking for 30 min, the intermediate was rinsed with ultrapure water and then vacuum dried at 40 °C for 36 h to obtain a Ru-loaded three-dimensional copper-based catalyst, which was designated as Ru-Cu(OH)2NW-CuCF-25.

[0072] After vacuum drying at 25°C for 36 h, it was found that there were still water marks on the surface of the intermediate and it could not be completely dried.

[0073] Comparative Example 2

[0074] The preparation method of a metal-supported three-dimensional copper-based catalyst comprises the following steps:

[0075] S1. After pickling 2cm×1cm copper foam in 3mol / L dilute sulfuric acid solution for 30min, rinse with ultrapure water, dry at 60℃ for 6h, and take out to obtain clean copper foam.

[0076] S2. Soak the clean copper foam in a mixed solution containing 0.05 mol / L ammonium persulfate and 1 mol / L sodium hydroxide for 30 min, the volume of the mixed solution is 8 mL, then take it out and vacuum dry it at 95°C for 12 h to obtain Cu2O-Cu(OH)2 nanowire-foam copper, recorded as Cu2O-Cu(OH)2NW-CuCF.

[0077] S3. Immerse the Cu2O-Cu(OH)2NW-CuCF in 5 mL of a 2 mmol / L metal solution containing HAuCl4 as the solute. After shaking for 30 min, rinse with ultrapure water and vacuum dry at 40 °C for 36 h to obtain an Au-loaded three-dimensional copper-based catalyst, which is designated as Au-Cu(OH)2NW-CuCF-95.

[0078] Examples 1 to 6 of the present invention all prepare metal-supported three-dimensional copper-based catalysts. The metal-supported three-dimensional copper-based catalysts prepared in Examples 1 to 5 are taken as examples and compared with Comparative Examples 1 to 2. The specific research methods and results are as follows:

[0079] via Figure 1 It can be seen that after loading different metal nanoparticles on the Cu(OH)2 nanowires, the obtained metal-loaded three-dimensional copper-based catalysts exhibit different macroscopic color changes, indicating that different metal-loaded three-dimensional copper-based catalysts are generated.

[0080] Figure 2 to Figure 5The results in Figure (a) show that the metal-supported three-dimensional copper-based catalysts obtained in the present invention all have a nanowire structure, and have a multi-dimensional structure of two-dimensional copper-based hydroxide nanowires modified by nanoparticles grown on three-dimensional copper foam. Figure 2 to Figure 5 The results in Figure (b) show that the particle size of Ru nanoparticles is 39.41nm, the particle size of Pd nanoparticles is 91.92nm, the particle size of Au nanoparticles is 99.97nm, and the particle size of Au / Ru nanoparticles is 58.75nm. There are many chemical adsorption active sites, and the metal nanoparticles do not agglomerate. Figure 2 to Figure 5 The results in Figure (c) show that the metal-supported three-dimensional copper-based catalyst products obtained in Examples 1 to 4 are pure and not doped with other elements.

[0081] Figure 6 The catalytic performance diagrams of the metal-loaded three-dimensional copper-based catalysts and copper foam of Examples 1 to 4 are as follows. The catalytic method is as follows: the metal-loaded three-dimensional copper-based catalysts or copper foam of Examples 1 to 4 are used as working electrodes, Ag / AgCl is used as a reference electrode, and a platinum mesh is used as a counter electrode. Reactions are carried out in an H-type electrolytic cell, K2SO4 solutions are added to the cathode and anode, respectively, and 10 mmol / L KNO3 solution is added to the cathode at the same time. A -0.4 V vs. RHE voltage is provided to the working electrode by an electrochemical workstation for a 2 h it test to test the nitrate conversion rate and synthetic ammonia yield of the working electrode. Figure 6 The results show that the metal-supported three-dimensional copper-based catalyst obtained by the present invention has good nitrate conversion rate and synthetic ammonia yield, has high performance of electro-reduction of nitrate to produce ammonia, and its performance is significantly better than that of foam copper.

[0082] Figure 7 The results in Figure (a) show that under vacuum drying conditions at 90°C, the active sites of Cu2O are reduced, and Au nanoparticles are obviously distributed in the defective area at the top of the Cu(OH)2 nanowires, with a significantly reduced number. Figure 7 The results in Figure (b) show that the size of Au nanoparticles is significantly increased compared with Example 3. Figure 7 The results in Figures (c) and (d) show that the nitrate conversion rate and the synthetic ammonia output are significantly reduced compared with Example 3.

[0083] Figure 8 The results in Figure (a) show that if the Cu(OH)2 nanowires are dried below 30°C and then reacted with metal ions, they will react with the metal ions to produce cuprous oxide, and then there will be no Cu(OH)2 nanowire structure. Figure 8 Figure (b) shows the nitrate conversion rate of Ru-Cu(OH)2NW-CuCF-25, indicating that the performance is significantly reduced without Cu(OH)2 nanowires.

[0084] Fig. 9 The results show that after drying at a vacuum drying temperature higher than 90°C, micro-local Cu network melting will occur, causing uncontrollable random damage, affecting the quality of Au-Cu(OH)2NW-CuCF-95 and reducing the catalytic performance.

[0085] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a metal-supported three-dimensional copper-based catalyst, characterized in that: The following steps are involved: The copper foam is immersed in a mixed solution containing ammonium persulfate and sodium hydroxide, then taken out and vacuum dried at 30°C to 90°C. Under this drying condition, Cu(OH)2 nanowires grow on the copper foam, and part of the Cu(OH)2 is dehydrated and reduced to Cu2O, thereby obtaining Cu2O-Cu(OH)2 nanowire-copper foam; The Cu2O-Cu(OH)2 nanowire-foam copper is immersed in a metal solution and mixed, and Cu2O reduces the metal ions to metal to obtain a metal-supported three-dimensional copper-based catalyst.

2. The method for preparing a metal-supported three-dimensional copper-based catalyst according to claim 1, characterized in that: The metal ion in the metal solution is selected from Pd 2+ 、Ru 3+ 、Au 3+ One or more of the .

3. The method for preparing a metal-supported three-dimensional copper-based catalyst according to claim 1, characterized in that: The molar concentration of metal ions in the metal solution is 2 mmol / L to 5 mmol / L.

4. The method for preparing a metal-supported three-dimensional copper-based catalyst according to claim 1, characterized in that: The vacuum drying time is 12h to 24h.

5. The method for preparing a metal-supported three-dimensional copper-based catalyst according to claim 1, characterized in that: The time for immersing Cu2O-Cu(OH)2 nanowire-foam copper in the metal solution is 5min to 30min.

6. The method for preparing a metal-supported three-dimensional copper-based catalyst according to claim 1, characterized in that: In the mixed solution, the concentration of sodium hydroxide is 0.8 mol / L to 1.5 mol / L, and the concentration of ammonium persulfate is 0.03 mol / L to 0.07 mol / L.

7. The method for preparing a metal-supported three-dimensional copper-based catalyst according to claim 1, characterized in that: The solvents of the mixed solution and the metal solution are both ultrapure water, and the resistivity of ultrapure water is 18.25 MΩ·cm.

8. The method for preparing a metal-supported three-dimensional copper-based catalyst according to claim 1, characterized in that: The time for immersing the foam copper in the mixed solution is 25 minutes to 35 minutes.

9. A metal-supported three-dimensional copper-based catalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: In the metal-supported three-dimensional copper-based catalyst, Cu(OH)2 nanowires are distributed on the copper foam, and one or more metal nanoparticles of Au, Ru, and Pd are located on the surface of the Cu(OH)2 nanowires.

10. Use of the metal-supported three-dimensional copper-based catalyst according to claim 9 in preparing an electrode material for electrocatalytic reduction of nitrate to ammonia.

Citation Information

Patent Citations

  • Catalyst as well as preparation method and application thereof

    CN118847149A

Cited By

  • Preparation method and application of Al-doped CuO nanosheet electrocatalyst

    CN119824460A